Double manual versus automated cleaning of loaner depth gauges used in clinical practice - Boff, Isabela Marra de Queiroz; Costa, Dayane de Melo; Goulart, Débora Moura Miranda; Pereira, Luiz Antônio; dos Santos, Michelle Augusta; Leão Vasconcelos, Lara Stefânia Netto de Oliveira; Tipple, Anaclara Ferreira Veiga (International Journal of Infection Control, 2023)
Background: Automated cleaning is recommended for reprocessing complex design surgical instruments, as it is reproducible and cleaning parameters can be controlled. However, automated equipment may not be a reality for many hospitals, particularly in lower-middle income countries. Objective: The aim of this study was to compare the effectiveness of double manual cleaning and automated cleaning of depth gauges in use in clinical practice and supplied in a loaner system. Design: Twenty four depth gauges available for use in a loaner system were evaluated before double manual cleaning (Group 1) or immediately after double manual cleaning (Group 2), or automated thermal disinfector cleaning (Group 3) or automated ultrasonic cleaning (Group 4). Thereafter, the depth gauges in each group were analysed by visual inspection (n = 24), bacterial culture (n = 12), and adenosine triphosphate (ATP) test (n = 12). Results: Stains, grooves, oxidation or visible debris were detected on at least one of the depth gauges from each group, and most were positive for bacterial growth (n = 11/12). Cleaning methods significantly reduced the amount of ATP (P < 0.05), except for automated ultrasonic cleaning. Conclusions: Double manual cleaning of depth gauges was similar to automated cleaning in a thermal disinfector, suggesting the possibility for implementing double manual cleaning as an alternative in sterilising service units where automated cleaning equipment is not avaliable.